Diagnostic Test Development for Uncovering Student Misconceptions in Mechanical Wave Characteristics Topic - Nurohmah, Aneu Siti; Samsudin, Achmad; Rusnayati, Heni; Sozbilir, Mustafa (Universitas Islam Negeri Raden Intan Lampung, 2025)
High school students have studied the characteristics of mechanical waves, including definitions, types, physical quantities, and properties of waves. However, many students still hold misconceptions about these concepts. This study aims to describe the validity and reliability of the Four-Tier Mechanical Wave Characteristics (FTMWC) diagnostic test instrument, developed to identify misconceptions among high school students regarding mechanical wave characteristics. The FTMWC was created through development research using the 4D model (Define, Design, Develop, Disseminate). The study involved 112 grade XI high school students who had already studied mechanical waves and were selected using purposive sampling. The instrument was analyzed using the Rasch Model with Winsteps software version 3.73. The validity of the FTMWC instrument was confirmed based on item dimensionality. The construct validity yielded a Cronbach's Alpha value of 0.61, indicating that the instrument sufficiently explains the interaction between participants and items. The item reliability was found to be 0.95, categorized as